EVALUATION OF MODIFICATED STEEL SCAFFOLD APPLICATION AS A TEMPORARY SUPPORT FOR THE TRANSFER BEAM COLUMN STRUCTURE (CASE STUDY : TUNJUNGAN PLAZA 6 PROJECT IN SURABAYA): Evaluasi Terhadap Penggunaan Perancah Baja Modifikasi sebagai Penopang Sementara untuk Struktur Transfer Beam Column (Studi Kasus Proyek Tunjungan Plaza 6 Surabaya) - Nugraha, Herdhyasmara Rizki; Arifin, Syamsul; Wahyuningtyas, Winda Tri (Universitas Jember, 2018)
Scaffolding is one of the important components in the concrete job. Its role of supporting the work of concrete, the structure of scaffold should be taken into account appropriately. Failure in planning of the scaffold will result disturb on a concrete job. Along with the development of the times, the construction services company developed a method in the work of the scaffolding. One example that is replace the scaffolding with steel profiles. The purpose of the advent of modificated steel scaffold is to allow the structure of the scaffold to be able to sustain a larger burden compared with the structure of the scaffolding. Behind the goals to be achieved, there is the risk that may occur. For example, swelling costs resulting from the use of steel profiles for the components of the structure of the scaffold. Therefore, must to be evaluated so as to achieve greater efficiency in terms of steel profile dimensions as well as the cost product of use modificated steel scaffold. Modificated steel scaffold in Tunjungan Plaza 6 projects were used to shore up the structure Transfer Beam named megatruss. From the results of this research obtained efficiency of steel profile dimensions for the scaffold structure. So obtained also the efficiency to cost product the use of scaffolding megatruss is equal of 20,05%. Perancah merupakan komponen penting dalam pekerjaan beton sehingga struktur harus diperhitungkan dengan tepat. Kegagalan dalam perencanaan perancah akan berakibat pada kegagalan struktur saat pekerjaan beton. Saat ini perusahaan jasa konstruksi mengembangkan metode dalam pekerjaan perancah, salah satu contohnya yaitu mengganti struktur perancah (scaffolding) dengan perancah dari profil baja. Tujuan munculnya perancah baja modifikasi ini adalah untuk memungkinkan struktur perancah untuk dapat menopang beban yang lebih besar dibandingkan dengan struktur perancah (scaffolding) pada umumnya. Dampak dari perubahan perancah berakibat pada pembengkakan biaya akibat dari penggunaan profil baja. Oleh sebab tersebut, maka perlunya dilakukan evaluasi agar tercapainya efisiensi dari segi dimensi profil bajanya serta biaya produksi dari penggunaan perancah baja modifikasi. Perancah baja modifikasi pada proyek Tunjungan Plaza 6 Surabaya yang digunakan untuk menopang struktur Transfer Beam Column diberi nama megatruss. Dari hasil penelitian ini didapatkan hasil bahwa diperoleh efisiensi dimensi profil baja untuk struktur perancah tersebut. Sehingga diperoleh pula efisiensi untuk biaya produksi (cost product) penggunaan perancah megatruss yaitu sebesar 20,05%.